Poland’s Breast Self-Exams: Empowering Awareness - Krużel, Aleksandra; Kłos, Kamil; Sajdak, Piotr; Tomasik, Justyna; Dębik, Marika; Stodolak, Marcel; Szydłowski, Łukasz; Żurowska, Klaudia; Ziajor, Seweryn; Bednarski, Artur (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Breast cancer poses a significant global health challenge, especially in Poland, where it is the most prevalent cancer among women. Despite advancements in medical technology, individual awareness and proactive health practices, such as Breast Self-Examination (BSE), are crucial for early detection. This study focuses on BSE practices in the Tarnów district of Poland, a small city facing unique healthcare challenges, to understand the prevalence, knowledge, and attitudes toward BSE. The aim of study was to comprehensively investigate BSE practices among women in the Tarnów district, considering socio-demographic factors. Material and Methods: Anonymous questionnaires assessed socio-demographic characteristics, attitudes toward BSE, frequency of BSE performance, knowledge on BSE, and sources of information. The survey involved 100 Polish women in gynecologist and general practitioner offices in Tarnów County. Results were analyzed in relation to age, education, and place of residence. Results: While 90% of women were familiar with BSE, 10% had never heard of it. While 29% performed BSE monthly, 18% never conducted the examination. Knowledge gaps were identified, particularly regarding optimal BSE practices. Information sources included the Internet (44%) and gynecologists (28%). Notably, 65% expressed a willingness to participate in BSE training. Conclusions: In conclusion, the study provides valuable insights into BSE practices among women in the Tarnów district, emphasizing the need for targeted interventions to encourage regular BSE. Knowledge gaps and the willingness of women to participate in training present opportunities for healthcare initiatives. The study also highlights the need for broader health education campaigns to dispel myths and enhance awareness, particularly regarding breast cancer affecting both genders. Limitations include a small sample size and geographic specificity to Tarnów district.